STOC Free: An Innovative Framework to Compare Probability of Freedom From Infection in Heterogeneous Control Programmes - van Roon, Annika M.; Santman-Berends, Inge M. G. A.; Graham, David; More, Simon J.; Nielen, Mirjam; Madouasse, Aurélien; Mercat, Mathilde; Fourichon, Christine; Gethmann, Jörn; Frössling, Jenny; Lindberg, Ann; Correia-Gomes, Carla; et al. (Frontiers in Veterinary Science, 2019)
The existence, stage of eradication and design of control programmes (CPs) for diseases that are not regulated by the EU differ between Member States. When freedom from infection is reached (or being pursued), safe trade is essential to protect (or reach) that status. The aim of STOC free, a collaborative project between six countries, is to develop and validate a framework that enables a transparent and standardized comparison of confidence of freedom for CPs across herds, regions or countries. The framework consists of a model combined with a tool to facilitate the collection of the necessary parameters. All relevant actions taken in a CP are included in a Bayesian network model, which allows prior distributions for most parameters. In addition, frequency of occurrence and risk estimates for factors that influence either the probability of introduction or temporary misclassification leading to delayed detection of the infection are included in the model. Bovine viral diarrhoea virus (BVDV) is used as an example disease. Many countries have CPs in place for BVDV and although elements of the CPs are similar, biosecurity measures and testing protocols, including types of tests and testing frequency, as well as target groups, differ widely. Although the initially developed framework is based on BVDV, the aim is to make it sufficiently generic to be adaptable to CPs for other diseases and possibly other species. Thus, STOC free will result in a single general framework, adaptable to multiple disease CPs, which aims to enhance the safety of trade.